Myocardial Revascularization in Patients with Coronary Artery Disease and Reduced Left Ventricular Ejection Fraction - Mariia V. Kucheriava; Georgiy B. Mankovsky (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To evaluate the short-term and long-term outcomes of myocardial revascularization – percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) – in patients with coronary artery disease (CAD) and heart failure (HF) with reduced left ventricular ejection fraction.Materials and methods. This one-center prospective study was conducted on the basis of the Ukrainian Children’s Cardiac Center, Clinic for Adults, Kyiv, Ukraine. Analysis included 194 patients with CAD and HF with reduced left ventricular ejection fraction. The studied cohort of patients underwent myocardial revascularization: 99 (51.1%) patients through PCI and 95 (48.9%) patients through CABG during 24 months (between January 2020 and January 2022).Results and discussion. PCI and CAD were associated with a similar risk of all-cause mortality during 30-day follow-up (HR 0,95; [95% CI], 0.135-6.796; p=0.96). When analyzing the long-term results of myocardial revascularization in terms of the effect on all-cause mortality, PCI and CABG had identical results, no significant difference was observed (HR 1.05; [95% CI], 0.448-2.481; p = 0.903). However, PCI was associated with an increased risk of repeated myocardial revascularization (HR 3.00; [95% CI], 1.251-7.221; p=0.025) compared with CABG. Patients who underwent CABG had a significant difference in the number of re-hospitalizations due to HF progression compared to those after PCI (HR 0.33; [95% CI], 0.170-0.652; p=0.002). The rehabilitation period was 2±4 days in patients after PCI, and 7±4 days in patients after CABG, which corresponded to a statistically significant difference (HR 3.48; [95% CI], 2.489-4.891; p <0.001). The visual analog scale scores of pain intensity were 3±1 in patients after PCI and 7±2 in those after CABG, the difference is statistically significant (HR 3.16; [95% CI], 2.283-4.382; p <0.001).Conclusions. Results of myocardial revascularization with PCI and CABG had identical short-term and long-term all-cause mortality rates. However, PCI was associated with a higher risk of repeated myocardial revascularization over a 2-year follow-up period. CABG, in turn, was associated with more frequent HF readmissions than PCI. The rehabilitation period was statistically shorter in patients after PCI. According to the visual analog scale, the pain in patients after CABG was more pronounced.